The Existence of Oral Traditions in Indonesia - Siti Indriyani Hulumudi; Yudi Sukmayadi (Edumaspul: Jurnal Pendidikan, 2025)
This article discusses oral traditions in Indonesia, especially in the Gorontalo community. The aim is to examine the extent of the process of maintaining and developing the oral tradition in Gorontalo, especially the form of reciprocal rhyme called Pa'iya lo hungo lo poli. This type of rhyme is sung by two young people taking turns, and the rhyme consists of four lines in each stanza, and each stanza is followed by a response to the rhyme which has the same rhyme and rhythm. This pantun can also be a means of social communication and fun entertainment for the people of Gorontalo. What is researched is the process of learning the Pa'iya lo hungo lo poli pantun, and what is the context of life values that can be learned from it through the behavior shown by the supporting community. The research results show that the pantun learning process is carried out non-formally, especially on a community basis through oral traditions passed down between generations, especially among families, and has an impact on the expression of a harmonious life based on the noble values found in the meaning of pantun poetry. This reflection is also part of efforts to preserve and promote the existence of the Pa'iya lo hungo lo poli pantun as part of Gorontalo's local cultural heritage.